Sorting of an apical plasma membrane glycoprotein occurs before it reaches the cell surface in cultured epithelial cells (The Rockefeller University Press, 1984)
In Madin-Darby canine kidney (MDCK) cells (a polarized epithelial cell line) infected with influenza virus, the hemagglutinin behaves as an apical plasma membrane glycoprotein. To determine biochemically the domain on the plasma membrane, apical or basolateral, where newly synthesized hemagglutinin first appears, cells were cultured on Millipore filters to make both cell surface domains independently accessible. Hemagglutinin in virus-infected cells was pulse-labeled, chased, and detected on the plasma membrane with a sensitive trypsin assay. Under all conditions tested, newly made hemagglutinin appeared simultaneously on both domains, with the bulk found in the apical membrane. When trypsin was continuously present on the basolateral surface during the chase, little hemagglutinin was cleaved relative to the amount transported apically. In addition, specific antibodies against the hemagglutinin placed basolaterally had no effect on transport to the apical domain. These observations suggested that most newly synthesized hemagglutinin does not transiently appear on the basolateral surface but rather is delivered directly to the apical surface in amounts that account for its final polarized distribution.